The Case of Sustainability Assurance: Constructing a New Assurance Service* - O’Dwyer, Brendan (Contemporary Accounting Research, 2011)
This paper presents an in-depth longitudinal case study examining the processes through which practitioners in two Big 4 professional services firms have attempted to construct sustainability assurance (independent assurance on sustainability reports). Power’s (1996, 1997, 1999, 2003) theorization of the way in which new subject areas are made auditable is used to frame the findings. The case analysis reveals the fragile nature of efforts to innovate with sustainability assurance and render sustainability reporting auditable. It suggests that innovation in new assurance practices may be constrained by an over-reliance on traditional financial audit training and techniques and certain internal professional services firm control procedures. Practitioners are shown to have experienced considerable discomfort in their attempts to construct a stable and legitimate knowledge base for assurance practice. Tacit knowledge embedded in highly subjective assessments of evidence has been frequently enrolled to make assurance possible in the presence of vague guidance from assurance standards. In light of ongoing practitioner struggles, both firms have publicly acknowledged the limitations of traditional financial audit practice operating alone in the conduct of sustainability assurance. In order to offset these limitations, they have proposed a coupling of ‘‘expert’’ stakeholder assessments of reporting completeness with traditional audit assessments of data reliability. This assigns part of the responsibility for delivering on a key assurance objective (reporting completeness) to what many practitioners perceive as questionable stakeholder expertise. The findings extend prior research highlighting the trial and error nature of the processes through which accountants seek to develop their presence in new markets for their expertise. They also question the extent to which the core aims being espoused for sustainability assurance can be substantively aligned with the operational capabilities available within Big 4 professional services firms.